Cover Feature: Towards Solving the PFAS Problem: The Potential Role of Metal‐Organic Frameworks (ChemSusChem 19/2022). Issue 19 (19th September 2022) - FitzGerald, Laura I.; Olorunyomi, Joseph F.; Singh, Ruhani; Doherty, Cara M.
Abstract : The Cover Feature shows an enzyme encapsulated with a metal–organic framework (MOF) degrading a perfluoroalkyl and polyfluoroalkyl substance (PFAS). PFAS are highly recalcitrant molecules that are linked to negative health outcomes. MOFs are tunable and porous materials with ultra‐high internal surface areas that can protect proteins from harsh conditions, preventing denaturation. They have also been shown to be effective catalysts, adsorbents, and useful in sensing so have potential in addressing the difficult problem of PFAS decontamination. The protein structure for this image was obtained from RSCB PDB (PDB ID: 1SUV). More information can be found in the Review by L. I. FitzGerald et al .